(untitled) (One Health Journal of Nepal, 2022)
Introduction: Sleep Quality is an essential component of the learning and memory processes. Nevertheless, sleep issues are common among college students and may negatively impact their academic performance. This study aimed to explore sleep quality among undergraduate nursing students in Nepal. Methods: We conducted a cross-sectional descriptive study among 267 nursing students from seven colleges located in Kathmandu Valley. A self-administrated questionnaire was distributed among students to assess sleep quality. We used the Pittsburgh Sleep Quality Index (PSQI) to determine sleep quality. Collected data was entered and analyzed in SPSS version 18. Results: Of total, 97 students (36.3%) were found to have good sleep quality, whereas 170 students (63.7%) were found to have poor sleep quality. Conclusions: Poor sleep quality was common among nursing students and may have negative effects on both health and academic performance. Nursing students should be actively intervened upon to enhance their sleep hygiene.